Analysis of Sugar Beet Pulp by X-ray Photoelectron Spectroscopy - Jiang, Guilin (2005)
Determining the chemical structure and composition of biomass fuels using x-ray photoelectron spectroscopy (XPS) can provide fundamental knowledge of their structures that is useful in understanding and predicting their combustion behavior. Sugar beet pulp is an example of an agricultural residue (byproduct of food and feed production) of potential interest for biomass combustion. The XPS spectra of sugar beet pulp provide both its elemental composition and indications of its bonding. Traditional fuel analyses of this fuel are also provided. These include: ultimate analysis — the elemental composition of the overall fuel (C, H, N, S, and O); chlorine analysis — reported here as part of the ultimate analysis but formally a separate procedure; proximate analysis — the proximate composition of the fuel (moisture, fixed carbon, volatiles, and ash); heating value — the specific heat of combustion. These data are summarized with the XPS spectra.